The complete mitochondrial genome of Mong Cai pig (Susscrofa) in Vietnam - Thuy Nhien Thi Tran; Pan Ni; Jianhai Chen; Thuy Thi Le; Kemp, Stephen J.; Han Jianlin; Haiyan Wang; Zhao, Shuhong (Informa UK Limited, 2016)
The Mong Cai pig is an indigenous breed and popularly raised as maternal line in northern Vietnam. In this study, the complete mitochondrial genome sequence of the Mong Cai pig is reported. The total length of this mitochondrial genome is 16 632bp, including 1 non-coding control region (D-loop region), two ribosomal RNA genes, 13 protein-coding genes and 22 transfer RNA genes. The phylogenetic tree of 162 pig complete mitogenomes reveals a very close relationship between Mong Cai pig in Vietnam and Bama miniature pig in southern China. This complete mitochondrial genome sequence of Mong Cai pig is useful to further genetic studies on adaptation and performance.